Designing a model for assessing organizational justice orientation - Pourbarchi, Zahra Akbari; Habibollah Salarzehi, Mehdi Kazemi, Amin Reza Kamaliyan, Seyed Aligholi Rowshan, (Opción, 2019)
The present study aims to identify and shape the dimensions and components of organizational justice orientation with a qualitative approach. In this study, a meta-synthesis (MS) method was adopted to identify the key aspects of organizational justice orientation. The results of the MS indicated that the dimensions of organizational justice and their components were crucial. In conclusion, the differentiation between organizational justice as practice and behavioral ethics as moral standards makes us perceive one another as relatively independent variable that can influence or be related to each other in informative ways